Answer:
(1, -1, 3)
Explanation:
Given system of linear equations is,
2x + 3y - 2z = -7 ---------- (1)
x - 2y + 4z = 15 ------- (2)
2y + z = 1 ------------ (3)
Equation (2) multiplied by 2 then subtracted from equation (1),
(2x + 3y - 2z) - 2(x - 2y + 4z) = -7 - 30
(2x - 2x) + (3y + 4y) + (-2z - 8z) = -37
7y - 10z = -37 ------ (4)
Equation (3) multiplied by 10 then added to equation (4),
(20y + 10z) + (7y - 10z) = 10 - 37
27y = -27
y = -1
From equation (3),
2(-1) + z = 1
-2 + z = 1
z = 3
From equation (2),
x - 2(-1) + 4(3) = 15
x + 2 + 12 = 15
x + 14 = 15
x = 1